(untitled) (Neo Science Peer Reviewed Journal, 2023)
Information is given about the history of several unique schools of painting in Uzbekistan, the unique styles of the Tashkent school of painting, the creation and development of the Ferghana school of painting, the Khorezm school of painting, the Bukhara and Samarkand schools of painting. villages. In addition, information is provided on the history of wood carving and the creative activities of its schools and craftsmen. The great contribution of master carvers to the development of woodcarving is noted.